Peredaran Etomidate Lintas Negara di Kawasan Asia Tenggara dan Dampaknya terhadap Keamanan Manusia di Indonesia - Ramsan Siregar; Stanislaus Justin Ananta; Matthew Witjaksono Rahardjo; ⁠Palupi Anggraheni (Jurnal Sosial Humaniora, 2026)
The circulation of New Psychoactive Substances (NPS) represents an increasingly multidimensional non-traditional security challenge, particularly when medical substances such as etomidate are misused through electronic cigarette devices (e-cigarettes). This study analyzes the cross-border dissemination of etomidate in Southeast Asia and its implications for human security in Indonesia. Using a qualitative approach with a phenomenological emphasis, this research draws on primary data obtained through interviews with the Indonesian National Narcotics Board (BNN), complemented by secondary data from international studies, policy documents, reports, and media coverage. The findings reveal that the dissemination of etomidate exploits regulatory gaps, product innovation, and adaptive Transnational Organized Crime (TOC) networks, with adolescents identified as the primary target group. From the perspective of Asia’s communitarian-oriented human security framework, the misuse of etomidate threatens not only individual well-being but also social resilience, collective values, and community stability. This study suggests that while law enforcement remains an essential component in addressing this issue, its effectiveness needs to be strengthened through social support derived from families and communities. Accordingly, reinforcing family- and community-based protection frameworks, such as the Family UNited approach, constitutes a more contextual and sustainable preventive strategy in responding to the growing threat of synthetic narcotics in Indonesia.